KEPESERTAAN BPJS KESEHATAN SEBAGAI SYARAT WAJIB BAGI PENDAFTARANPERALIHAN HAK ATAS TANAH ATAU HAK MILIK ATAS SATUAN RUMAH SUSUN KARENA JUAL BELI - Cindy Meyloni Gabriela Bedu; Pan Lindawaty S. Sewu; Daniel Hendrawan (Universitas Negeri Makassar, 2023)
The government through the Ministry of ATR/BPN has issued Circular Letters (SE) Number HR.02/153-400/II/2022 and HR.02/164-400/II/2022. The circular requires that the sale and purchase of land must attach a BPJS Health membership card. The writing of this scientific paper uses a normative juridical approach method, based on literature research that includes primary, secondary, and tertiary legal materials then analyzed using qualitative methods. This research results that the policy issued by the government aims to optimize the implementation of the National Health Insurance program, increase access to quality health services, and ensure the sustainability of the National Health Insurance program in line with the principle of legal expediency (zwech matigheid or doelmatigheid or utility).